The impact of Nodes Distance on Wireless Energy Transfer System - Risma, Pola; Dewi, Tresna; Oktarina, Yurni (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2020)
Wireless energy transfer (WET) reemerges as the method for transmitting electric power without the necessity to deal with cable losses and an aesthetically pleasing environment. The problem with WET is how to maintain magnetic induction as the distance gets further. This paper investigates the impact of nodes distance on the WET system. The experimental results show that the most effective distance among transmitter, nodes, and receiver are 4 cm. The measurement is taken with and without load. The without load application give that for node 1; the results are 6 V, 110 mA, and 2.85 mT for voltage, current, and magnetic flux, respectively. At the application of 2 nodes, the voltage is 6.8 V, the current is 0.124 mA, and the magnetic flux is 3.83 mT, and at three nodes installation, it is 7 V, 134 mA, and 3.83 mT. During the application of 3-Watt and 5-Watt lamp, at 4 cm distance, the power received is 1.66 W and 3.66 W at 3-Watt and 5-Watt lamp for one node, 1.84 W, and 3.84 for two nodes, and 1.93 W and 3.93 for three nodes. The experimental results show that the transmitted signal can be prolonged by installing nodes. Even though this study shows that 4 cm is the most effective, it is possible to increase up to 20 cm to power a 3-Watt lamp and 5-Watt lamp.